2004
DOI: 10.1002/hyp.1464
|View full text |Cite
|
Sign up to set email alerts
|

Regional daily baseflow prediction

Abstract: Abstract:The purposes of this study are to identify the bias of applying the analysis of a log-log plot of baseflow and to derive an equation to describe successive regional mean baseflow. The function dQ/dt D a Q b has been used to describe baseflow in many studies that obtain the values of a and b from the log-log plot. According to analysis in this study, the value of 1 can be assigned to b in two boundary conditions, but the parameter a is proved to be related to the depth of water table and starting time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…A common way to identify the groundwater infiltrations to stream is linked to the baseflow, which is defined as the net flow from groundwater storage to a stream (Singh, 1968). Baseflow has been used as an approximation of groundwater discharge and play an important role in water resources management (Szilagyi et al, 2003;Tung et al, 2004). Many investigations on baseflow characteristics, such as baseflow estimation (Singh, 1968;Reilly and Kroll, 2003), baseflow prediction (Tung et al, 2004), and impacted factors on the baseflow (Wittenberg, 2003;Kirk et al, 2008), have been used in some rivers.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A common way to identify the groundwater infiltrations to stream is linked to the baseflow, which is defined as the net flow from groundwater storage to a stream (Singh, 1968). Baseflow has been used as an approximation of groundwater discharge and play an important role in water resources management (Szilagyi et al, 2003;Tung et al, 2004). Many investigations on baseflow characteristics, such as baseflow estimation (Singh, 1968;Reilly and Kroll, 2003), baseflow prediction (Tung et al, 2004), and impacted factors on the baseflow (Wittenberg, 2003;Kirk et al, 2008), have been used in some rivers.…”
Section: Introductionmentioning
confidence: 97%
“…Baseflow has been used as an approximation of groundwater discharge and play an important role in water resources management (Szilagyi et al, 2003;Tung et al, 2004). Many investigations on baseflow characteristics, such as baseflow estimation (Singh, 1968;Reilly and Kroll, 2003), baseflow prediction (Tung et al, 2004), and impacted factors on the baseflow (Wittenberg, 2003;Kirk et al, 2008), have been used in some rivers. The changes of baseflow in response to human activities and climate changes have also been studied (Cooper et al, 1995;Wittenberg, 2003;Kirk et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For the case b D 3/2, the average discharge over a time interval t can be shown as Equation (A1) (see Equation (15) in Tung et al, 2004):…”
Section: Appendixmentioning
confidence: 99%
“…The recession analysis uses a log-log plot with time-averaged flows to estimate interception and slope of the Equation (1). Tung et al (2004) found that coefficient a is not always a constant. Instead, the coefficients are functions of initial water tables and the start time of a recession event.…”
mentioning
confidence: 99%
“…Tung et al (2004) point out a practical issue, which is the error introduced by using time-averaged values of discharge. The issue, however, is probably not serious for many practical applications and the error can be made negligible by using time intervals that are appropriate to the time rate of change in discharge.…”
mentioning
confidence: 99%